Paramedic Students' Knowledge, Attitudes, and Preparedness to Manage Intimate Partner Violence Patients. (2nd November 2017) - Sawyer, Simon; Coles, Jan; Williams, Angela; Lucas, Peter; Williams, Brett
Abstract: Background: Intimate partner violence (IPV) refers to abuse transpiring between people in an intimate relationship. Intimate partner violence is a leading cause of morbidity and mortality for women that paramedics frequently report encountering and yet paramedics rarely receive formal education or training to manage. The response of paramedics to IPV is likely to be directed by their individual knowledge, attitudes, and preparedness; all of which are currently unknown. This study aimed to measure paramedic students' knowledge, attitudes, and preparedness to manage IPV patients, and provides baseline data to inform the development of contemporary curricula.Methods: We surveyed a cohort of paramedic students from two Australian universities using the Modified Physician REadiness to Manage Intimate partner violence Survey (PREMIS). Internal consistency of previously identified scales was calculated and multiple linear regression was used to measure the association between previous training, knowledge, attitudes, and preparation.Results: We received 260 surveys (80.5% response rate). Results show that actual knowledge, perceived knowledge, and preparedness to manage IPV patients were low. Students with previous training reported higher perceived knowledge (p <.05) and preparedness (p <.01). Participants reported low self-efficacy, confidence, and preparation to manage IPV patients and demonstrated mostly neutral attitudes toward women and patients.Conclusions: Results indicate students require increased IPV education. Education should improve knowledge and preparedness to recognize and refer IPV patients, as well as change neutral and inappropriate attitudes. Incorporating such education and training into the paramedic curricula may improve the preparedness of practitioners, resulting in an improved response to IPV patients.